2022
DOI: 10.3390/v14102162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Coronavirus Disease (COVID-19) in Mexican Children and Adolescents

Abstract: Background: We analyzed the demographic, clinical, and diagnostic data of children and adolescents in Mexico, from the first case of coronavirus disease (COVID-19) to 28 February 2022. Methods: Using the open databases of the Ministry of Health and a tertiary pediatric hospital, we obtained demographic and clinical data from the beginning of the COVID-19 pandemic until 28 February 2022. In addition, quantitative reverse-transcription polymerase chain reaction outputs were used to determine the viral load, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…As in previous studies, we observed that risk of hospitalization, emergency department visit, or unscheduled doctor visit (ie, health care utilization) in the 6 months leading up to the study visit was reduced with a history of COVID-19 vaccination or anti-N IgG, 6 , 7 although in our study COVID-19 vaccination may not have been available to all participants. Thus, health care utilization was observed to increase with allergen-specific atopy.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As in previous studies, we observed that risk of hospitalization, emergency department visit, or unscheduled doctor visit (ie, health care utilization) in the 6 months leading up to the study visit was reduced with a history of COVID-19 vaccination or anti-N IgG, 6 , 7 although in our study COVID-19 vaccination may not have been available to all participants. Thus, health care utilization was observed to increase with allergen-specific atopy.…”
Section: Discussionsupporting
confidence: 68%
“… 6 In a large Mexican study of COVID-19-related hospitalizations in children and adolescents, asthma was also identified as a comorbidity risk factor. 7 Asthma has also been implicated as a risk factor for post–COVID-19 syndrome in children and adolescents. 8 Currently, the US Centers for Disease Control and Prevention indicates that individuals with moderate to severe asthma are disproportionally affected by SARS-CoV-2 and are more likely to be hospitalized.…”
mentioning
confidence: 99%
“…At the end of 2020 and the rst half of 2021, Mexico was going through the most critical phase of infections and deaths related to COVID-19 (https://coronavirus.jhu.edu/region/mexico). Therefore, the epidemiological surveillance strategy implemented by the Mexican government included suspected cases (based on the clinical picture or an epidemiological association) and con rmed cases based on any of the following three processes: test con rmed by an authorized laboratory, epidemiological association with a case con rmed by a laboratory test, and cases con rmed by an opinion committee (only applicable for postmortem diagnosis) [24]. This implied that patients showing more than one symptom associated with SARS-CoV-2 infection were diagnosed as a probable case of COVID-19 without requiring a diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic data included sex and age, and clinical data included patient status, comorbidities, and signs/symptoms. The comorbidities were de ned by Flores-Alanis et al and the signs/symptoms were de ned by Cortés-Sarabia et al [24,59].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation